Physics of shock and impact. - Grady, D. E. (IOP (Series). Release 4., 2017)
Physics of Shock and Impact' deals with the shock physics of solids with emphasis on impact applications that are brought about by intense energy stimulation. Comprising two volumes, this work covers physical, material, mechanical and thermodynamic fundamentals of shock physics. The various chapters also include a range of analytic solutions that address topics in the many applications involving shock physics. Volume 1, Fundamentals and dynamic failure, provides an introduction to the fundamentals of shockwave physics and progresses to the modes of shock failure through spall, fragmentation and shear localization.